Vulnerability as potential: the search for agency in Deborah Levy’s _Hot Milk_ (2016) - Flores-Quesada, María Magdalena (My University, 2019)
Departing from Agamben’s idea of potentiality, I propose to explore this notion in connection to the critical term of vulnerability, to show that they are not that different as one could think at first. In order to do so, I will analyse the portrayal of vulnerability and potential in the contemporary novel _Hot Milk_ written by the Britisth author Deborah Levy and published in 2016.
Keywords: Literatura contemporánea; Literatura inglesa; Levy, Deborah; Agamben, Giorgio; British literature; Deborah Levy; Giorgio Agamben; Vulnerability; Contemporary literature; Ethics of alterity; The other